FAKTOR-FAKTOR YANG PENTING DALAM SISTEM PENILAIAN KOMPETENSI KONTRAKTOR BERDASARKAN PERSEPSI KONTRAKTOR DI KOTA PALU - Mangitung, Donny M. (MEKTEK, 2006)
Perception data of assessment of contractors’ competency is necessary to be collected from any parties who involve in construction projects in order to improve contractor selection system, not only in the stage of prequalification phase, but also in the stage of tender phase or in the stage of a selection of the winning contractor. To obtain the answer of contractors’ perception in terms of the most to the least important factors of the assessment of contractors competency, a structure questionnaire survey was conducted in Palu, where the sample came from a part of small contractors in Palu. Technical and managerial strength and compliance with regulations factors are the highest rank, while financial strength is the lowest rank. Moreover, positive correlations of the techncial and managerial strength exhibit statistically significant with other factors.